THE EFFECTIVENESS OF PARAGRAPH SHRINKING TECHNIQUE IN TEACHING READING TO JUNIOR HIGH SCHOOL: English - Imam Sagita (Journal of English Development, 2021)
ABSTRACT The main problem of this research was focused on the effective teaching reading comprehension by using paragraph shrinking technique to eight grade students at SMP Negeri 1 Bumi Agung. The objective of this thesis is to know the effectiveness of teaching reading comprehension by using paragraph shrinking technique to eight grade students at SMP Negeri 1 Bumi Agung. In writing this research, the researcher used experimental method. The researcher used two groups of students namely control group students at SMP Negeri 1 Bumi Agung in academic year 2013/2014 with total students were 108 from three classes. The form three classes the researcher took two classes as sample. It was 36 students of VII.A as experimental group and it was 36 students of VII.B as control group which chosen by using cluster random sampling. The data obtained from the test analyzed by using SPSS 19 paired sample t-test. Based on the study, the students in the experimental group who used paragraph shrinking have higher achievement in finding the main idea than the students in control group who did not use paragraph shrinking method. Learning reading thorough paragraph shrinking encourages students to learn more about main idea. It could be seen from their enthusiasm during the teaching learning process. Based on the calculation above, the researcher got the average score in control group was 58.83 and experimental group was 73.34. The standard error of control group was 1.43 and experimental group was 1.78. Meanwhile, its critical value at 5% (1.99) significant with df = 68 was 6.363, t-obtained 1.99 was higher than t-table as a critical value. In other words, Ho was rejected and Ha was accepted, it means that paragraph shrinking was significantly effective in teaching reading. Based on the finding discussed above, it could be concluded that it was significantly effective to applied paragraph shrinking method in teaching reading.